Angel C. Anden an annotated bibliography, 1928-1975 - Manalo, Alicia A.; Manuel, Arsenio E.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1977)
This special problem is a comprehensive, chronological listing of the editorials, essays, short stories, periodical articles, and other writings of Angel C. Anden for the period 1928-1975. During this period, this prolific author who is also a physical culturists, a veteran of World War II, and a scientific inventor, published at least 453 by-lined works. Not listed here are his numerous writings which do not bear his name nor his two pseudonyms, C. Prigo and Ruben Flores. A biographical sketch faithfully tracing his ancestry and parentage is also included.
Each of the entries in this bibliography is preceded by a 3-digit entry number, followed by the title and source of the work. The title of the periodical, volume and issue number, date, and page or pages in which the article appeared are indicated. The library or libraries in which the source is available are indicated in parentheses to complete the bibliographic entry. A descriptive annotation for each entry is provided. In most cases the subject of the article is indicated. However, short stories are simply identified as such in annotation. Subject and title indexes are provided.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Anden, Angel Calica -- Bibliography